AN EMPIRICAL ANALYSIS OF IMPACT OF TRAINING AND DEVELOPMENT ON EMPLOYEES IN DURGAPUR STEEL PLANT (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Iron and Steel Industry is one of the basic  industries of the country and plays a crucial  role in the development of the sustainable  society. Durgapur Steel Plant is one of the  integrated steel plants of SAIL and it plays an  important role in the industrial development  of India. It is in this context after reviewing the  literature of the effect of training on employee  performance in different sectors it was found  that no significant studies are there to ascertain  the effectiveness of training in steel sector. This  paper carried out a detailed study to find out  the impact of different variables on training  and development of employees and how to  overcome shortcomings in training so that  employees can work in effective manner in  Durgapur Steel Plant.
Keywords: Durgapur Steel plant(DSP); Training; Development